Efanesoctocog alfa elicits functional clot formation that is indistinguishable to that of recombinant factor VIII. (22nd May 2022) - Demers, Melanie; Aleman, Maria M.; Kistanova, Elena; Peters, Robert; Salas, Joe; Seth Chhabra, Ekta
Abstract: Background: Factor VIII (FVIII) binding to endogenous von Willebrand factor (VWF) has constrained half‐life extension of recombinant FVIII (rFVIII) products for hemophilia A. Efanesoctocog alfa (rFVIIIFc‐VWF‐XTEN; BIVV001) is a novel fusion protein designed to decouple FVIII from VWF in circulation and maximize half‐life prolongation by XTEN ® polypeptides and Fc fusion. FVIII, VWF, and platelets interact to achieve normal hemostasis. Thus, bioengineered FVIII replacement products, such as efanesoctocog alfa, require comprehensive assessment of their hemostatic potential. Objectives: We compared functional clot formation and injury‐induced platelet accumulation between efanesoctocog alfa and rFVIII. Patients/Methods: The hemostatic potential of efanesoctocog alfa and rFVIII were assessed by measuring their dose‐dependent effects on in vitro fibrin generation in hemophilic plasma and in vivo injury‐induced platelet accumulation using intravital microscopy and repeat saphenous vein laser‐induced injuries in hemophilia A mice. Results: Equal concentrations of efanesoctocog alfa or rFVIII (up to 1 IU/ml) added to plasma from patients with hemophilia A elicited similar kinetics for dose‐dependent fibrin polymerization between factor products. In the presence of tissue plasminogen activator (tPA), clots formed had similar stability between products. Single intravenous doses (50, 100, or 150 IU/kg) of efanesoctocog alfa or rFVIII shortly before repeat saphenous vein laser‐induced injuries increased platelet accumulation over time in a dose‐dependent manner in hemophilia A mice. Platelet deposition kinetics were similar between products. Conclusions: Equivalent doses of efanesoctocog alfa and rFVIII had similar efficacy in promoting fibrin clot formation and injury‐induced platelet accumulation. The hemostatic potential of efanesoctocog alfa was indistinguishable from that of rFVIII.